Long-term prognosis of patients with cancer-related genes detected in postoperative peritoneal washings obtained during curative gastrectomy. Issue 1 (January 2022) - Takebayashi, Katsushi; Murata, Satoshi; Kodama, Hirokazu; Kaida, Sachiko; Yamaguchi, Tsuyoshi; Ishikawa, Ken; Shimoji, Miyuki; Miyake, Toru; Ueki, Tomoyuki; Kojima, Masatsugu; Iida, Hiroya; Maehira, Hiromitsu; et al.
Abstract: Background: Cancer cells in intraoperative peritoneal washings (PW) indicate increased peritoneal recurrence. Detection of CEA or CK20 genes indicates poor prognosis. We assessed long-term prognosis of patients with amplification of cancer-related genes in PW obtained intraoperatively during curative gastric cancer surgery. Methods: PW was collected before and immediately after curative gastrectomy. CEA, CK20, TFF1, MUC2, and FABP1-mRNA were selected as marker genes for reverse transcription polymerase chain reaction. Peritoneal recurrence-free survival (PRFS) and overall survival (OS) after >7-year follow-up were examined using the Kaplan–Meier method. Results: Of 138 patients who underwent gastrectomy with negative cytological findings at laparotomy, 80 patients showed negative cancer-related gene amplification in preoperative PW. Fifty-eight patients were excluded due to positive gene amplification, which suggested presence of preoperative peritoneal cancer cells. The 80 patients had mRNA amplification in PW after surgery. Amplification of multiple and single cancer-related marker genes was observed in 38 and 21 patients; 21 cases had marker-negative results. Five-year PRFS was 69.1%, 95.2%, and 100% in multi-marker-positive, single marker-positive, and marker-negative cases, respectively. Multi-marker-positive patients had significantly worse PRFS than the other groups ( p  < 0.05). Multivariate analysis in the Cox proportional hazards model identified multi-marker-positivity as an independent prognostic factor for PRFS (hazard ratio, 7.6; 95% confidence interval, 1.07–62.63; p  = 0.046), and multi-marker-positive patients had significantly worse OS than other groups ( p  < 0.01). Conclusion: Multi-marker cancer-related gene amplification in PW is associated with worse prognosis in PRFS and OS even after a long follow-up; PRFS can be stratified by the number of genes amplified.